Juvenile Nasopharyngeal Angiofibroma- Analysis of Intraoperative Bleeding in Patients Undergoing Preoperative Embolization vs. Carotid Artery Ligation - Baig, Maria; Javaid, Waqas (Biological and Clinical Sciences Research Journal, 2025)
A rare vascular tumor called Juvenile Nasopharyngeal Angiofibroma causes severe bleeding during its surgical removal. To determine whether the procedure significantly reduces intraoperative blood loss, this study compares carotid artery ligation with preoperative embolization. Objectives: To compare the efficacy of preoperative embolization versus external carotid artery ligation in reducing intraoperative blood loss in patients undergoing surgical resection for Juvenile Nasopharyngeal Angiofibroma (JNA). Methodology: This prospective, randomized, controlled trial was conducted over a 6-month period, from March 1, 2024, to August 31, 2024, at the Department of ENT, Sir Ganga Ram Hospital, Lahore. After ethical approval, forty male JNA patients (Radkowski Stage II & III) were randomly assigned to two groups. Twenty Group A patients had super-selective embolisation of the tumor-feeding arteries 24–72 hours before surgery. Twenty patients in Group B had the ipsilateral external carotid artery (ECA) surgically ligated at least 24 hours before final excision. The same ENT doctor performed all tumour resections endoscopically. Millilitres of intraoperative blood loss were the primary outcome measure. Secondary outcomes included blood transfusions, surgery duration, and complications. Results: The mean intraoperative blood loss was significantly lower in Group A (Preoperative Embolization) (645 ± 215 mL) compared to Group B (Carotid Ligation) (1185 ± 430 mL) (p < 0.001). Consequently, the intraoperative blood transfusion requirement was also significantly lower in Group A (1.1 ± 0.7 units) than in Group B (2.8 ± 1.2 units) (p < 0.001). The mean duration of surgery was shorter in Group A (145 ± 35 minutes) than in Group B (195 ± 45 minutes) (p = 0.002). No significant complications related to the embolization procedure were noted. Conclusion: Preoperative super-selective embolization is a significantly more effective adjunctive procedure than external carotid artery ligation in reducing intraoperative blood loss and transfusion requirements during surgical resection of JNA. It should be considered the gold standard preoperative preparation for JNA where interventional radiology expertise is available.